ALAT BUKTI LABORATORIUM FORENSIK DALAM PERKARA PIDANA PEMBUNUHAN: Studi kasus: Nomor: 181/Pid.B/2024/PN Kbj - Romi Ginting (NERACA KEADILAN, 2025)
Forensics (derived from the Latin "forensis" meaning "from outside", and is akin to the word forum meaning "public place") is a field of science that is used to assist the process of enforcing justice through the process of applying knowledge or science. In this group of forensic sciences, among others, forensic physics, forensic chemistry, forensic psychology, forensic medicine, forensic toxicology, forensic psychiatry, forensic computers, and so on. This study uses a normative juridical research method, namely research on legal norms that are linked to library data related to forensic laboratory evidence in Criminal Case Number 181 / Pid.B / 2024 / PN KBJ. While data analysis is carried out qualitatively which is sourced from library data and interviews with samples in this study. After conducting research on laboratory evidence in proving the criminal case of murder Number 181 / Pid.B / 2024 / PN Kbj. It can be concluded, among others, that forensic laboratory evidence is very important in proving criminal cases of murder, obstacles in the investigation of forensic laboratory evidence include, long distance from the crime scene, limited costs, contamination of four incidents by the community.